Distribution of PCV13 and PPSV23 Streptococcus pneumoniae serotypes in Argentinean adults with invasive disease, 2013-2017 - Zintgraff, Jonathan (2020)
Fil: Zintgraff, Jonathan. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Bacteriología. Servicio de Bacteriología Clínica; Argentina.